Pengaruh Sulfat Terhadap Kuat Tekan Beton dengan Variasi Bubuk Kaca Substitusi Sebagian Semen dengan w/c 0,60 dan 0,65 - Fikkriansyah .; Gunawan Tanzil (Jurnal Teknik Sipil dan Lingkungan, 2013)
Increase of cement price, causing the cost of concrete production more expensive. To overcome this problem is to utilize industrial wastes. The most potential is waste glass, that when the form of very fine powder showed pozzolan properties because it contains SiO2. And to improve the durability of concrete, sulfate-resistant concreteÂ  studied. Cement in concrete is replaced by glass powder with the proportion of 0%, 5%, 10% 15% and 20%. Cylindrical specimens were made with two different mix designs (w/c 0,6 and 0,65) is calculated based on ACI method. Specimens soaked in two types of water, plain water and magnesium sulfate solution for 7, 21, and 28 days. Komala Sari (2011) examined a concrete with glass powder as a cement replacement percentage up to 20% glass powder, obtained the 5% glass cement replacement concrete achieve maximum compressive strength. From the research, obtained found that only the 5% glass cement replacement concrete that reached the design strength. The compressive strength of the 5% glass cement replacement concrete was the maximum compressive strength. While the concrete with 15% and 20% glass replacement has a smaller compressive strength than normal concrete. Keywords : Compressive strength, glass powder, sulfate solution s